LncRNA-TUG1: Implications in the Myocardial and Endothelial Cell Oxidative Stress Injury Caused by Hemorrhagic Shock and Fluid Resuscitation - Wei Li; Huaiyu Chen; Xueli Zhu; Mingrui Lin (Frontiers in Bioscience-Landmark)
Background: LncRNA taurine-upregulated gene 1 (TUG1) can regulate vascular endothelial cell injury, a critical mechanism in treating hemorrhagic shock and fluid resuscitation (HS/R). Therefore, this study explored the influence of TUG1 in HS/R. Methods: An in vivo rat model of ischemia-reperfusion (I/R) injury post-HS/R and an in vitro model of oxidative stress injury in rat cardiomyocyte cell line (H9C2) were constructed. In vivo, we silenced TUG1 and quantified its expression along with inflammatory factors through quantitative reverse transcription polymerase chain reaction (qRT-PCR), mean arterial pressure (MAP) detection and blood gas analysis. Myocardial functional impairment was assessed via Triphenyl-2H-Tetrazolium Chloride (TTC), Hematoxylin and eosin, and Terminal deoxynucleotidyl transferase-mediated deoxyuridine triphosphate nick end labeling (TUNEL) stainings. Oxidative stress level in rat serum was measured. In vitro, we examined the changes of cell viability, apoptosis, oxidative stress levels, inflammatory factor secretion and nuclear factor-κB (NF-κB)/p65 expression by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT), flow cytometry, Enzyme-linked immunosorbent assay (ELISA) and Western blot. Results: TUG1 level was elevated in rats of I/R model caused by HS/R. TUG1 silencing ameliorated the decline in MAP, acid-base imbalance and myocardial tissue damage, and suppressed oxidative stress and inflammatory factor levels in model rat. TUG1 silencing enhanced viability, impeded apoptosis, and reduced oxidative stress, inflammatory factor contents and NF-κB/p65 expression in H2O2 treated H9C2 cells. Conclusion: TUG1 participates in regulating oxidative stress damage and inflammation induced by HS/R.